Rare bird documentation form for Glaucous Gull at Saylorville Dam, 1986 - Moore, Francis L.et al (1986)
Rare bird documentation form for a Glaucous Gull at Saylorville Dam in Polk County, IA on November 26, 1986. Epson - sheet feed